GH hormone replacement in adults: risk-benefict analysis (Revista Brasileira Multidisciplinar, 2026)
Growth hormone deficiency is a clinical condition resulting from decreased secretion of growth hormone (GH), which leads to several disorders, so replacement therapy has been used as a treatment for over 30 years. The aim is to understand the negative and beneficial effects of GH replacement. Methodology: In this literature review, the MEDLINE, PUBMED and SCIENCE DIRECT databases were used with the descriptors “Hormone Replacement Therapy”, “pituitary growth hormone” and “Long Term Adverse Effects”, filters were applied from the last 10 years (2014 to 2024), full and free texts, and in the end, 14 works that addressed the theme were used. Among the positive effects of using GH replacement therapy, there is an improvement in body composition, physical fitness and muscle strength, an increase in bone mineral density, lipid profile and cardiovascular inflammatory markers. On the other hand, among the adverse effects, there may be hyperglycemia, insulin resistance, risk of neoplasia, peripheral edema, and hormonal axis dysregulation. From treatment with GH, it is seen that the adverse effects differ according to the patient's profile, highlighting age, gender, and pre-existing comorbidities, and therefore, an individualized assessment of the risks and benefits must be made, while the beneficial effects that the treatment offers are indisputable, and these are independent of the particularities of each patient, with proven improvement in quality of life and reduction of complications, concluding that the benefits outweigh the possible adverse effects that the patient may develop.
Keywords: Therapeutics; Patients; Benefits; Risk; Growth hormone